Contraceptive use and method mix dynamics in Sub-saharan Africa: time trends and the influence of the HIV pandemic - Ayaga A. Bawah; Pearl S. Kyei; Charles Agyei-Asabere (BMC, 2024)
Abstract Background Contraceptive use dynamics continue to be of priority in sub-Saharan Africa because of persistently high levels of fertility. This paper focuses on the use of barrier versus non-barrier contraceptive use in sub-Saharan Africa hypothesizing that the HIV pandemic in the region would be responsible for increases in the use of barrier methods over time. Methods This paper uses Demographic and Heath Survey (DHS) data from 32 countries to conduct extensive analysis of trends in contraceptive use and method mix that refers to the distribution of contraceptive methods use among the sexually active population. The paper examines how contraceptive method mix dynamics have changed over time and whether the trends differ by marital status and gender using cross-tabulations. It furthers examines the determinants of method choice using logistic regressions. Results The findings indicate that the use of barrier methods, most markedly for unmarried women and men, rose substantially between the late 1980s and late 2000s in the region in tandem with trends in HIV prevalence. The results further show marked differences in method mix by gender with men being more likely to report barrier method use than women. Conclusions The findings indicate shifting preferences in contraceptive choice. The time trend analyses highlight the importance of expanding the focus of contraceptive use studies beyond women in this context as the study finds differing trends for men. Graphical Abstract